PENGARUH AGENCY COST TERHADAP NILAI PERUSAHAAN PADA SUBSEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Nurmalasari, Pratiwi; Maradesa, Djeini (Universitas Sam Ratulangi, 2021)
Competition between companies that are very tight in this modern era requires every company to maximize the value of the company so that the company is able to keep up with changes in order to survive in running the business. The purpose of this study is to determine the effect of agency costs on firm value in the property and real estate sub-sectors listed on the Indonesia Stock Exchange for the 2016-2020 period. This study uses a quantitative approach. The sampling method used is the purposive sampling method. The research sample used was 120 property and real estate companies listed on the IDX. The analytical tool used is simple linear regression. The results show that agency costs have no effect on firm value. which means that partially there is no significant effect between agency costs on firm value in the property and real estate sub-sectors listed on the Indonesia Stock Exchange for the 2016-2020 period.